Surface Contamination and Dose Rate Verification of Fertilizers common in Iraqi Plantations using RadEye B20 Detector - A. Baqir, Yassir; Farhan Kadhim, Nada (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Twenty three samples of granular chemical fertilizers and organic fertilizers commonly utilized in Iraqi ranches were collected. The samples were prepaid and stored in a Marinelli beaker to measure; dose rate, general count rate and surface contamination of the samples using the RadEye B20 detector, firstly with shield, secondly without the shield to estimate the effect of shielding on the measurements. The results showed that using shield made a significant decrease in the radiation measurements reached about 25%. However the mean value of surface contamination, dose rate and general count rate with shield were 0.54Bq/cm2, 0.65Âµsv/h, and 0.28Cps respectively, and without shield being 0.34Bq/cm2, 1.33Âµsv/h, and 1.52Cps respectively.